Large-scale simultaneous synthesis of highly photoluminescent green amorphous carbon nanodots and yellow crystalline graphene quantum dots at room temperature. Issue 15 (11th July 2017) - Liu, Meng Li; Yang, Lin; Li, Rong Sheng; Chen, Bin Bin; Liu, Hui; Huang, Cheng Zhi
Abstract : The room temperature synthesis of highly PL CNDs and GQDs by simply mixing TETA and p -benzoquinone and the origin of their photoluminescence. Abstract : Photoluminescent (PL) carbon dots (CDs) as a new type of carbon nanomaterial have attracted increasing attention owing to their fascinating properties. Herein, we develop a facile, energy-efficient, large-scale route to prepare highly PL CDs with a quantum yield of up to 35.3% at room temperature. These PL CDs can be further separated out into green-emissive amorphous carbon nanodots (CNDs) and yellow-emissive crystalline graphene quantum dots (GQDs) through a silica gel column. Both the as-prepared CNDs and GQDs, even when having the same particle-size distribution and chemical groups, have different degrees of surface oxidation. As characterized by X-ray photoelectron spectroscopy (XPS), the yellow-emissive crystalline GQDs have a much higher surface oxidation degree than that of the green-emissive amorphous CNDs. A further finding is that the characteristic emission peaks of the CDs show an obvious red shift from 518 nm to 543 nm with the increase in the surface oxidation degree, which can be attributed to the decrease in their band gap between the lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO). That is, the difference in band gap is closely related to the oxidation degree of the CDs, rather than the particle size or chemical groups. Moreover, the amorphous CNDs are very easily photobleached under 140 W xenon lamp irradiation as compared to the crystalline GQDs, indicating that the photostability is dependent on the crystalline structure of the CDs, which is beneficial for the top-down design and development of suitable CDs for different application purposes.